The End of Deportation - Cházaro, Angélica (UCLA law review, 2021)
This Article introduces to legal scholarship a new horizon for pro-immigrant scholarship and advocacy: deportation abolition. The ever-present threat of deportation shapes the daily lives of noncitizens. Instead of aiming for a pathway to citizenship, most noncitizens must now contend with dodging the many pathways to banishment. Despite growing threats to immigrant survival, most pro-immigrant scholarship and advocacy that aims to reduce migrant suffering assumes deportation as inevitable. The focus remains on improving individual outcomes by aligning the process of deportation with due process and the rule of law. But considered from the point of view of those facing deportation, even a fairly adjudicated deportation can prove devastating. Moreover, none of the improvements in deportation management can eliminate the racialized violence that defines the practice. While post-entry social control and extended border control purportedly justify deportation, the stated goals of deportation law obfuscate its true character as an indefensible act of violence. The underlying assumption that deportation can and should continue indefinitely currently demarcates the outer limits of the arguments for addressing deportation-limits that a commitment to deportation abolition would abandon. In an effort to denaturalize the common sense of deportation, this Article explores the fundamental failures that characterize the practice. By questioning commonly held assumptions about its inevitability, critiquing reform proposals that reify its logic, and providing examples of interventions that point toward the possibility of its demise, this Article opens the door to the end of deportation. decarceral demands made by social movements.